The bake shop ghost - Ogburn, Jacqueline K.; Priceman, Marjorie (New York Houghton Mifflin, 2005)
Miss Cora Lee Merriweather haunts her bake shop after her death, until the new shop owner makes a deal with her.
b
b
NP
Keywords: Ghosts -- Fiction; Cake -- Fiction; Bakers and bakeries -- Fiction